Perusahaan (Study Kasus Pada Koperasi Usaha Maju Analisis Arus Kas Dalam Menentukan Tingkat Likuiditas Bersama) - Irna Nopiana; Wiwi Warsiati (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The objek of this research is cash flow to the current ratio of the at koperasi usaha maju berasam the research method used is a quantitative method in the form of quantitative (amount),and is presented systematically.In this study there are two cariables,name cash flow (independent)Current ratio (dependent).the metode of analysis used in this study is the test of the correlation coefficient of determination and the regression equation.Base on the results of the test using SPSS,the results are aimed at knowing and studying the effect of cash flow variables on current ration,koperasi maju Bersama company for the period of 2017 -2020 the data use is secondary data in the form of annual data taken from annual reports.From the research,it is concluded that cash flow has an influence on the current ratio.where the coeffient of determination of cash flow,whit a current ratio of 0.996, this show the amount of contribution between cash flow,with a current ratio of 99.1% in addition,the level of significance between cash flow and the current ratio of 0.004<0.0050 Ho is reject,which means that ther is significant influence significantly.simultaneously cash flow to current ratio Keywords : Cash Flow Current ratio